Skrifgesag en prediking - Vos, Casparus Johannes Adam (Verbum et ecclesia, 1988)
Scriptural authority and preaching The point of departure for this article is that the Word of God has authority. Although there is formal concensus of opinion about this basic premise among the different schools of thought, there are important and even fundamental and unique differences of interpretation among them.